2014
DOI: 10.1517/14656566.2014.890590
|View full text |Cite
|
Sign up to set email alerts
|

Current pharmacotherapy for obesity: extrapolation of clinical trials data to practice

Abstract: Drugs currently approved for long-term therapy of obesity offer modest benefits for most patients, substantial benefits for some and no benefits for others. Numerous methodological problems including exclusion of the type of patients who are most often seen in clinical practices, inadequate enrollment of men and minorities, exclusion of patients taking antidepressants, high dropout rates, lack of follow-up after treatment discontinuation, and less than ideal imputation methods in data analysis limit the interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Obesity is a chronic condition that cannot be ameliorated simply with lifestyle behavior alone [1,2]. Obesity contributes to insulin resistance, type 2 diabetes (T2DM) and is associated with a host of comorbidities and therefore represents a healthcare crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a chronic condition that cannot be ameliorated simply with lifestyle behavior alone [1,2]. Obesity contributes to insulin resistance, type 2 diabetes (T2DM) and is associated with a host of comorbidities and therefore represents a healthcare crisis.…”
Section: Introductionmentioning
confidence: 99%
“…To add complexity in drug development in this therapeutic area, it has been reported that numerous methodological problems limit the interpretation of clinical trial data and their generalizability [199]. Moreover, the landscape of antiobesity drugs is also hampered by the reduced effect of antiobesity drugs outside clinical trials with respect to that exerted in a clinical trial setting, with a behavioral and dietetic support [189].…”
Section: Targetmentioning
confidence: 99%
“…The most effective currently available anti-obesity drug phentermine/topiramate combination therapy has the severe teratogenic risk of cleft lip with or without cleft palate. 42 Women are required to have a negative pregnancy test prior to taking the drug, but should also use highly effective contraceptives. 42 …”
Section: Bariatric Surgerymentioning
confidence: 99%
“…42 Women are required to have a negative pregnancy test prior to taking the drug, but should also use highly effective contraceptives. 42 …”
Section: Bariatric Surgerymentioning
confidence: 99%